2023
DOI: 10.1149/1945-7111/acbfe5
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Electro-organic Synthesis and Functionalization of Catechol Derivative on Carbon Black and Its Interference-free Voltammetric pH Sensor Application

Abstract: We report an easy electrochemical route for preparing a catechol derivative (di-ferulyl sesamol derivative, designated as CA-Fer) functionalized low-cost carbon black (CB) modified electrode in a neutral pH buffer solution. As synthesized precursor organic compound, CA-Fer has been electrochemically oxidized over the CB by potential cycling treatment in pH 7 PBS that leads to a high redox active CA-Fer-catechol derivative (CB@CA-Fer-Redox), which exhibited a well-defined and stable surface-confined redox resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Similar non Nernstian gradients were found with the LIG-Riboflavin system when switching between 2-electrode and 3-electrode configurations. It is noteworthy that Srinivas et al (2022) also observed a similar non Nernstian (2H + /3e − ) behaviour (45 mV) with a carbazole-quinone derivative and attributed the response to the orientation/interaction of the redox probe on the surface [ 70 ]. The change in behaviour upon being surface confined is supported by the work by Lee et al (2013) where the pKa and hence protonation of the redox species can be modified by the surface interactions [ 73 ].…”
Section: Resultsmentioning
confidence: 98%
“…Similar non Nernstian gradients were found with the LIG-Riboflavin system when switching between 2-electrode and 3-electrode configurations. It is noteworthy that Srinivas et al (2022) also observed a similar non Nernstian (2H + /3e − ) behaviour (45 mV) with a carbazole-quinone derivative and attributed the response to the orientation/interaction of the redox probe on the surface [ 70 ]. The change in behaviour upon being surface confined is supported by the work by Lee et al (2013) where the pKa and hence protonation of the redox species can be modified by the surface interactions [ 73 ].…”
Section: Resultsmentioning
confidence: 98%